Aetiology of Ocular Surface Foreign Bodies and Correlation with Their Location in the Eye - Ahmad Zeeshan Jamil, Muhammad Sarwar Kha, Muhammad Luqman Ali Bahoo (Pakistan Journal of Ophthalmology, 2018)
Purpose: To find the aetiology of ocular surface foreign bodies and correlation with their location in the eye. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at Shahida Islam Teaching Hospital affiliated with Shahida Islam Medical College, Lodhran from November 2016 to October 2017. Material and Methods: 796 patients with ocular surface foreign bodies were included in this study. Age and gender were recorded for all patients. Detailed slit lamp examination was performed. Location of the foreign body was noted. Superficial foreign bodies were removed with the help of forceps. In case of impaction in the ocular surface foreign bodies were removed with the help of sterile 27/26 gauge needle. Results: Corneal injuries were most common. Most common location for different foreign bodies is as follows: metallic particle at cornea in 104 eyes (13.1%), insect wing in upper lid sub tarsal space in 75 eyes (9.3%), straw particles at cornea in 60 eyes (7.5%), piece of plastic at cornea in 24 eyes (3.0%), whole insect or fly in inferior fornix in 12 eyes (1.5%), thread/cloth particle in upper lid sub tarsal space in 17 eyes (2.1%), dust particles at cornea in 54 eyes (6.8%) and contact lens in the superior fornix in 2 eyes (0.3%). Conclusion: Most common aetiology of ocular surface injury was metallic particle and most common location was cornea. No statistically significant correlation has been found between the aetiology of ocular surface foreign body and their location in the eye. Key words: Foreign bodies, Ocular, Metallic, Corneal injuries.